The Impact of Using Technology in Improving Student Achievement in Intensive Reading at St Augustine Hippo Catholic University - Tuminah; Julis (PT FORMOSA CENDEKIA GLOBAL, 2022)
The development of technology greatly influences human life, as well as in the world of education. The use of smartphones has become a necessity for students even in increasing achievement. The purpose of this study was to describe the effect of Smartphone use on Intensive Reading learning achievement in St Augustine Hippo Catholic University students. The rapid development of information technology has affected all aspects of human life. In addition, the development of information and communication technology has a positive impact on humans but can also have a negative impact, especially on mobile communication devices (smartphones). The method used in this research is quantitative research with a survey design. The results of the study show several important points, namely: (1) Increasing student learning outcomes in Intensive Reading, (2) Students are more active in carrying out learning activities in class, and (3) The quality of the teaching and learning process increases significantly. It can be concluded that the use of smartphones can improve student achievement.